The crisis of the political left in Northern Europe (the example of the Labour Party in Norway) - Ivan R. Skripka (Научно-аналитический вестник Института Европы РАН)
The article examines the crisis of the Northern European left-wing political forces using the weakening position of the Norwegian Labour Party in the 2020s as an example. It analyzes the impact of foreign policy tensions, economic difficulties, internal party scandals and changes in voter preferences on the party’s decline in popularity. Particular attention is paid to the results of local elections, which showed a significant decrease in support for the LP against the backdrop of the growth of right-wing forces. The article examines the reasons for the party’s loss of contact with its traditional base, including the working class and youth, as well as the growing dissatisfaction with the policies of its leader, Jonas Gahr Støre. The article emphasizes the need to adapt the LP’s ideology and strategy to new challenges, including environmental and social problems, in order to restore its position. Based on an analysis of political trends in Northern Europe, the author suggests possible ways to overcome the crisis.